FIRST EXPERIENCE WITH HEART TRANSPLANTATION IN KRASNODAR REGION - K. O. Barbukhatti; E. D. Kosmacheva; N. V. Kizhvatova; E. V. Gordeeva; E. D. Aleksandrova; L. K. Kruberg; O. A. Pozdnyakova; C. A. Raff; I. I. Yakuba; V. A. Porkhanov (Вестник трансплантологии и искусственных органов)
The article presents the 2-year results of prospective study, which included 67 heart transplantations for end-stage heart failure, performed in Krasnodar, in Clinical regional hospital No 1. Survival rate was 89,1% (59 patients). Causes of death were septic complications, thromboembolia of the pulmonary artery, severe pancreatonecrosis, and transplant rejection due to non-compliance with immunosuppression therapy, heart rhythm disturbances. The most common complications were pneumonia (19%), heart graft rejection (10%), steroid-induced diabe- tes (10%). In a year after heart transplantation chronic heart failure, II stage, was diagnosed in 29 patients (43%), I stage – in 30 (44%) patients. Monitoring and therapy are carried out by cardiologists domiciliary and by spe- cialists of polyclinic of Krasnodar clinical hospital. Orthotopic heart transplantation is an effective treatment for end – stage heart failure. It is possible to provide surgical treatment and further management of patients in multisectoral regional medical hospital.